EVALUASI BELAJAR PESERTA DIDIK (SISWA) - ., Mahirah B (Idaarah: Jurnal Manajemen Pendidikan, 2017)
Education is the most important investment for every nation especially for the developing nation, which actively builds its country. Development can only be done by human beings prepared through education, in order to reach the most perfect man as the caliph above earth. The development of education or teaching is inseparable and the responsibility of an educator, how the educator is transforming the knowledge possessed by the existing teaching materials, and by paying attention to the method of teaching that is easily accepted by the learners so that the goal is achieved in accordance with what is expected. Objectives to be achieved then the educator must malakukan an activity called the evaluation of education. Evaluation is part and process of learning which in whole can not be separated from teaching activity, conducting evaluation which is done in education activity has a very main meaning, because evaluation is a measuring tool or process to know level of achievement that have been achieved by student of material or material has been submitted, so that with the evaluation of the objectives of the learning will be seen accurately and convincingly. Evaluation as part of a learning program needs to be optimized, as it not only relies on assessments of learning outcomes, but also needs assessment of inputs, processes, and outputs. One of the important factors for the effectiveness of learning is the evaluation factor both on the learning process and on the learning outcomes. Evaluation is a systematic collection activity of the learning process to determine whether changes occur to students and to what extent these changes affect the life of the students.